Protective Effect of Amphipterygium adstringens Extract on Dextran Sulphate Sodium-Induced Ulcerative Colitis in Mice - Mario Rodriguez-Canales; Ruben Jimenez-Rivas; Maria Margarita Canales-Martinez; Ana Judith Garcia-Lopez; Nelly Rivera-Yañez; Oscar Nieto-Yañez; Yadira Ledesma-Soto; Luvia Enid Sanchez-Torres; Miriam Rodriguez-Sosa; Luis Ignacio Terrazas; Marco Aurelio Rodriguez-Monroy (Mediators of Inflammation)
Amphipterygium adstringens is an endemic species in Mexico commonly known as “cuachalalate.” Healers to treat gastritis, gastric ulcers, and gastrointestinal cancer have traditionally used the bark. We investigated the effects of alcoholic extract of A. adstringens (AaEE) in DSS-induced colitis in mice. The protective effect of AaEE was determined at 200 mg/kg by oral gavage for 10 days. We determine the effect of AaEE on clinical features (disease activity index), antioxidants, anti-inflammatory, and immunomodulatory activities in relation to the activity of SOD, CAT, and GPx, levels of proinflammatory cytokines, and changes both macroscopic and microscopic of the colonic mucosa. AaEE significantly reduced the inflammation of colon and significantly increased SOD and GPx activities. AaEE also significantly decreased TNF-α, IFN-γ, and IL-1β cytokine levels compared to DSS-treated mice and reduced both infiltration of inflammatory cells and the mucosal damage in colon. The results suggested the protective potential of AaEE in DSS-induced colitis and this might be attributed to its phytochemicals compounds that have been found to induce a wide spectrum of activities such as reduction in oxidative stress, suppression of inflammation, modulating numerous signal transduction pathways, and induction of apoptosis. The findings of this study suggest that AaEE has substantial potential for the treatment of inflammatory colitis.